If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4w + -13w = 36 Combine like terms: 4w + -13w = -9w -9w = 36 Solving -9w = 36 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Divide each side by '-9'. w = -4 Simplifying w = -4
| 49j^2+17j=0 | | 8×1/2= | | y-5=-5(x+4) | | 3x+3=-6x-6 | | 100=15t+5y | | 7(y-8)+6=-92 | | 12x=77 | | -2q-9=11+2q | | H(x)=x-8x+16 | | 5(x+2)-4= | | -2(2x+7)=-5+5x | | 3a+4(a+16)= | | 4.04=0.014x^2+0.89 | | 0.03x+.04(18000-x)=560 | | 9+3x-2= | | -p+4=25-8p | | 12.5m=32 | | m^2+49=0 | | 2p+p=90 | | 2x/3=5x-10/5 | | y-3.8y-6=-1.9y-11.4 | | 12x^2=77 | | (7-v)(4v-2)=0 | | 3(c+2)+1=5c-1 | | x^2+x=1.52 | | 509.8104=2*3.14*r^2+2*3.14*r*55.6 | | -7(-5k-7)=84 | | 5(k-3)=(k-5) | | (7x-15)1/3 | | 6(5/9) | | F(x)=(-6)+3 | | -1+20n+15=8n-10+6 |